Are home visits an effective method for diabetes management? A quantitative systematic review and meta‐analysis. Issue 5 (11th March 2017) - Han, Lin; Ma, Yuxia; Wei, Suhong; Tian, Jinhui; Yang, Xiaochun; Shen, Xiping; Zhang, Jun; Shi, Yuexian
Abstract : Home visits were associated with improved glycemic control and reduced cardiovascular risk factors, which indicates that it is an effective method for diabetes management. Abstract: Aims/Introduction: Previous reviews have revealed uncertainty regarding the effectiveness of home visit interventions for managing diabetes. Therefore, we carried out a quantitative systematic review and meta‐analysis to evaluate the effects of home visit interventions among patients with diabetes. Materials and Methods: We searched various electronic databases (PubMed, EMBASE, Cochrane Library, Web of Science, CINAHL, Wanfang and Chinese scientific full‐text databases) from their inception until March 2016. We included randomized controlled trials that included patients with diabetes, and evaluated the effects of home visit programs on glycated hemoglobin concentrations. Two reviewers independently used the Cochrane Collaboration methods to assess the included studies' risk of bias and quality. Results: We included seven randomized controlled trials with 686 participants. Compared with the usual care, the home visit group showed a greater reduction in glycated hemoglobin concentrations (mean difference −0.79% [−9 mmol/mol], 95% confidence interval [CI]: −0.93 to −0.25% [11 to −3 mmol/mol]; P  < 0.05; I 2  = 0%), systolic blood pressure (mean difference −5.94 mmHg, 95% confidence interval −11.34 to −0.54 mmHg) and diastolic blood pressure (mean difference −6.32 mmHg, 95% confidence interval −12.00 to −0.65 mmHg). Furthermore, home visits improved quality of life, high‐density lipoprotein, low‐density lipoprotein, total triglycerides and self‐management. However, there were no significant differences between the two groups in their bodyweight, total cholesterol, body mass index and self‐efficacy. Conclusion: Home visits were associated with improved glycemic control and reduced cardiovascular risk factors, which shows that it is an effective method for diabetes management.